Characteristics of service users and provider organisations associated with experience of out of hours general practitioner care in England: population based cross sectional postal questionnaire survey. (29th April 2015) - Warren, Fiona C; Abel, Gary; Lyratzopoulos, Georgios; Elliott, Marc N; Richards, Suzanne; Barry, Heather E; Roland, Martin; Campbell, John L
Abstract : Objective To investigate the experience of users of out of hours general practitioner services in England, UK. Design Population based cross sectional postal questionnaire survey. Setting General Practice Patient Survey 2012-13. Main outcome measures Potential associations between sociodemographic factors (including ethnicity and ability to take time away from work during working hours to attend a healthcare consultation) and provider organisation type (not for profit, NHS, or commercial) and service users' experience of out of hours care (timeliness, confidence and trust in the out of hours clinician, and overall experience of the service), rated on a scale of 0-100. Which sociodemographic/provider characteristics were associated with service users' experience, the extent to which any observed differences could be because of clustering of service users of a particular sociodemographic group within poorer scoring providers, and the extent to which observed differences in experience varied across types of provider. Results The overall response rate was 35%; 971 232/2 750 000 patients returned surveys. Data from 902 170 individual service users were mapped through their registered practice to one of 86 providers of out of hours GP care with known organisation type. Commercial providers of out of hours GP care were associated with poorer reports of overall experience of care, with a mean difference of −3.13 (95% confidence interval −4.96 to −1.30) compared with not for profit providers. Asian service users reported lower scores for all three experience outcomes than white service users (mean difference for overall experience of care −3.62, −4.36 to −2.89), as did service users who were unable to take time away from work compared with service users who did not work (mean difference for overall experience of care −4.73, −5.29 to −4.17). Conclusions Commercial providers of out of hours GP care were associated with poorer experience of care. Targeted interventions aimed at improving experience for patients from ethnic minorities and patients who are unable to take time away from work might be warranted.